Implementation of temperature and humidity monitoring system in wooden warehouse based on distance and access location assessment - Yuvina, Yuvina; Sundawa, Bakti Viyata; Setiawan, Bayu; Abdullah, Abdullah (Jurnal Mantik, 2025)
Indonesia is the largest furniture exporter in the world. This business will continue to grow because Indonesia has abundant wood raw materials. These wood raw materials must be stored in a good wooden warehouse because the bad warehouse conditions will cause physical damage to the wood. This study designed a temperature and humidity monitoring system in a miniature wooden warehouse based on Internet of Things (IoT) technology. The test location was carried out at 5 locations. The length of test time i.e. 8 hours. Based on testing, data are displayed in app.microthings.id website for access location of Medan Selayang, the max. temperature was 26.4oC and the max. humidity was 68.8%. For access location of Medan Baru on Berdikari road, the max. temperature was 26.4oC and the max. humidity was 68.8%. For access location of Medan Johor, the max. temperature was 25.4oC and the max. humidity 68.1%. For access location of Medan Baru on Jamin Ginting Road, the max. temperature was 25.1oC and the max. humidity was 68.3%. For access location of Medan Baru on Universitas road, the max. temperature was 24.7oC and the max. humidity was 69%. These data are compared to data from A-TH3 sensor. There is the difference and latency between them. The highest of latency occured in Medan Johor District about 10 second